PELAPISAN EMAS PADA KERAJINAN TANGAN PEWTER UNTUK MENINGKATKAN NILAI JUAL - Firlya Rosa (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2015)
Electroplating is process surface treatment on the electropolishing object or manually polishing objects to achieve higher value. Electroplating is the transfer of the metal ions with electric current through the electrolyte to create a layer on metal. Gold plating on pewter that  contain SN = 90-95%, Sb = 3-10%. and Cu = 1-3% aims to improve the quality of the surface of the object brighter and shiny. Initial coating with the appropriate current and the standard time immerse will produce perfectly electroplating metal. From the research, the initial coating using brass with brass plating, and initial coating using copper with copper cyanide solution will produce a brighter coating of gold and uniform weight of additional metal. Copper plating using copper with acid plating in higher current condition and long immersion will produce a black surface on pewter material.